Accessing indoor fungal contamination using conventional and molecular methods in Portuguese poultries - Viegas, Carla (2013)
Epidemiological studies showed increased prevalence of respiratory symptoms and adverse changes in pulmonary function parameters in poultry workers, corroborating the increased exposure to risk factors, such as fungal load and their metabolites. This study aimed to determine the occupational exposure threat due to fungal contamination caused by the toxigenic isolates belonging to the complex of the species of Aspergillus flavus and also isolates fromAspergillus fumigatus species complex. The study was carried out in seven Portuguese poultries, using cultural and molecularmethodologies. For conventional/cultural methods, air, surfaces, and litter samples were collected by impaction method using the Millipore Air Sampler. For the molecular analysis, air samples were collected by impinger method using the Coriolis μ air sampler. After DNA extraction, samples were analyzed by real-time PCR using specific primers and probes for toxigenic strains of the Aspergillus flavus complex and for detection of isolates from Aspergillus fumigatus complex. Through conventional methods, and among the Aspergillus genus, different prevalences were detected regarding the presence of Aspergillus flavus and Aspergillus fumigatus species complexes, namely: 74.5 versus 1.0% in the air samples, 24.0 versus 16.0% in the surfaces, 0 versus 32.6% in new litter, and 9.9 versus 15.9%in used litter. Through molecular biology, we were able to detect the presence of aflatoxigenic strains in pavilions in which Aspergillus flavus did not grow in culture. Aspergillus fumigatus was only found in one indoor air sample by conventional methods. Using molecular methodologies, however, Aspergillus fumigatus complex was detected in seven indoor samples from three different poultry units. The characterization of fungal contamination caused by Aspergillus flavus and Aspergillus fumigatus raises the concern of occupational threat not only due to the detected fungal load but also because of the toxigenic potential of these species.